2012
DOI: 10.21236/ada582232
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Mechanisms and Environmental Relevance of cis-Dichloroethene and Vinyl Chloride Biodegradation

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to the Department of Defense, Executive Services and Communications Directora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…As shown in Exhibit 2, at fEAFB there were some wells with very reducing geochemistry as evidenced by their <0.1 mg/L sulfate and >1 mg/L of methane, but there were other wells that were not nearly so reducing and contained up to 11 mg/L of sulfate and less than 0.1 mg/L of methane. Biodegradation of VC could occur through direct oxidation rather than reduction (Bradley, 2011;Bradley & Chapelle, 2011;Cox, 2010;Dijk et al, 2000;Gossett, 2010). Abiotic degradation (i.e., biogeochemical degradation) of the TCE and/or cDCE without production of VC (Brown et al, 2007(Brown et al, , 2009Ferrey et al, 2004) could also contribute to the attenuation processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Exhibit 2, at fEAFB there were some wells with very reducing geochemistry as evidenced by their <0.1 mg/L sulfate and >1 mg/L of methane, but there were other wells that were not nearly so reducing and contained up to 11 mg/L of sulfate and less than 0.1 mg/L of methane. Biodegradation of VC could occur through direct oxidation rather than reduction (Bradley, 2011;Bradley & Chapelle, 2011;Cox, 2010;Dijk et al, 2000;Gossett, 2010). Abiotic degradation (i.e., biogeochemical degradation) of the TCE and/or cDCE without production of VC (Brown et al, 2007(Brown et al, , 2009Ferrey et al, 2004) could also contribute to the attenuation processes.…”
mentioning
confidence: 99%
“…The geochemistry indicated reducing conditions throughout most of the plume, and the prevailing wisdom suggested that the only biodegradation active under such conditions was reductive dechlorination. However, remediation professionals now recognize the significance of abiotic degradation and even oxidative processes under reducing conditions (Bradley, 2011;Bradley & Chapelle, 2011;Cox, 2010;Dijk et al, 2000;Gossett, 2010). CSIA data were collected to review MNA at fEAFB, in part because CSIA is sensitive to all degradation: abiotic degradation, biodegradation, reductive dechlorination, and oxidation.…”
mentioning
confidence: 99%